Numerical Modelling of Deep Mixing in Passive Zone of an Excavation: A Case Study based on Västlänken E02 Centralen - Rehnberg, Oskar; Berghamn-Claesson, Marcus (My University, 2021)
This report focuses on how to model the short-term system response of a deep excavation with a lime cement column grid in the passive zone. The report investigates a case site in Gothenburg where a deep excavation is made in soft Scandinavian clay for the construction of a train tunnel. The investigation is conducted using a 2D homogenization technique in a finite element software. The clay is modelled using Creep-SCLAY1S and the LC using the Hardening Soil constitutive model. Results from the numerical investigation are compared with monitoring from the case study to analyse and reiterate. The comparisons show that the best method of modelling lime cement in this study is to have a homogenous soil body to represent the inner excavation. Installation effects of the lime cement has a considerable impact on the results. The lime cement columns decrease the horizontal displacements of the sheet pile walls in the excavation and the settlements on surrounding soil, while it increases the strut forces in the excavation due to its installation effects. Overall, deep excavations are complex systems. For accurate prediction of deformations during design, an understanding of the entire system will be necessary.
Keywords: Deep mixing; Plaxis 2D; passive zone; soft clay; Creep-SCLAY1S; Hardening soil; system response; lime cement installation effects; deep excavation